2020
DOI: 10.1155/2020/1878431
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Circular RNA DDX17 in Prostate Cancer

Abstract: Circular RNA DDX17 (circDDX17) has been demonstrated as a tumor suppressor in colorectal cancer. However, mechanisms underlying circDDX17 effects in cases of prostate cancer (PCa) are not well understood. Thus, herein, we determined measures of circDDX17 expression by use of the TCGA database. Expression of circDDX17 in prostate cancer-afflicted tissue samples was determined by qRT-PCR. Functionally, circDDX17 induced remarkable inhibition of cell colonizing ability, invasion, and epithelial-mesenchymal transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Many studies have found that circRNAs contain miRNA response element and they could work as endogenous miRNA ‘sponges’ to bind to miRNAs and then exert negative regulation on the expression of downstream genes. circDDX17 was implicated to regulate miR-605-cell cycle-related factors (cyclin dependent kinase 1 and p21), 27 miR-346/phospholysine phosphohistidine inorganic pyrophosphate phosphatase, 36 miR-31-5p-KN motif and ankyrin repeat domains1 28 axes. Mechanistically, circ-ELF2 acted as a ceRNA for miR-510-5p to positively modulate the expression of mucin 15 at posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found that circRNAs contain miRNA response element and they could work as endogenous miRNA ‘sponges’ to bind to miRNAs and then exert negative regulation on the expression of downstream genes. circDDX17 was implicated to regulate miR-605-cell cycle-related factors (cyclin dependent kinase 1 and p21), 27 miR-346/phospholysine phosphohistidine inorganic pyrophosphate phosphatase, 36 miR-31-5p-KN motif and ankyrin repeat domains1 28 axes. Mechanistically, circ-ELF2 acted as a ceRNA for miR-510-5p to positively modulate the expression of mucin 15 at posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“… 65 2019 circDDX17 hsa_circ_0063308 down miR-346 LHPP inhibited cell proliferation, invasion, and EMT 20 pairs of PCa tissues and adjacent normal tissues; 22Rv1 and PC-3 cell lines Lin et al. 99 2020 circCRKL hsa_circ_0001206 down miR-141 KLF5 repressed cell cycle, migration, and invasion, and boosted apoptosis 45 pairs of PCa tissues and adjacent normal tissues; LNCaP, DU145, C4-2, 22RV1, and RWPE-1 cell lines Nan et al. 100 2020 hsa_circ_0007494 hsa_circ_0007494 down miR-616 PTEN inhibited cell proliferation, migration, and invasion 49 pairs of PCa tissues and adjacent normal tissues; C4-2, PC3, 22Rv1, DU145, LNCaP, and RWPE-1 cell lines Zhang et al.…”
Section: Functions and Mechanisms Of Circrnas In Pcamentioning
confidence: 99%
“…95 In addition, Lin et al proposed that circDDX17 could inhibit proliferation, invasion, and EMT of PCa through the circDDX17/miR-346/LHPP signaling pathway. 99 Similarly, circAMOTL1L can upregulate the expression of E-cadherin by targeting the miR-193A-5P/PCDHA8 axis to prevent the metastasis of PCa. 65 In fact, the inhibition of EMT in PCa cells by p53 is also achieved through the circAMOTL1L/miR-193a-5P/PCDHA8 signaling pathway.…”
Section: Apoptosismentioning
confidence: 99%
“…circRNAs, with their multiple functions, are involved in many biological and pathological processes; they influence the progression of diseases, including viral infections and cancer [ 69 ]. In cancer, circRNAs influence the malignant phenotype by regulating specific cancer-related pathways and exert both an anti-cancer and pro-cancer action by acting as a tumor suppressor or oncogene [ 70 , 71 ]. They can be used as therapeutic targets in treatment.…”
Section: Circrnas As Biomarkers For Diseasesmentioning
confidence: 99%